2004
DOI: 10.1074/jbc.m313927200
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic Acid and Autotaxin Stimulate Cell Motility of Neoplastic and Non-neoplastic Cells through LPA1

Abstract: Autotaxin (ATX) is a tumor cell motility-stimulating factor originally isolated from melanoma cell supernatant that has been implicated in regulation of invasive and metastatic properties of cancer cells. Recently, we showed that ATX is identical to lysophospholipase D, which converts lysophosphatidylcholine to a potent bioactive phospholipid mediator, lysophosphatidic acid (LPA), raising the possibility that autocrine or paracrine production of LPA by ATX contributes to tumor cell motility. Here we demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
200
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(213 citation statements)
references
References 36 publications
13
200
0
Order By: Relevance
“…LPA, through LPA 1 receptor, stimulated glioma cell migration, while S1P, through S1P 2 receptor, negatively regulated the LPA action. LPA 1 -receptor-mediated migration has also been shown in the glioblastoma cell lines SF295 and SF539 (Hama et al, 2004). Previously, we reported that brain is one tissue in which S1P is abundantly present .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…LPA, through LPA 1 receptor, stimulated glioma cell migration, while S1P, through S1P 2 receptor, negatively regulated the LPA action. LPA 1 -receptor-mediated migration has also been shown in the glioblastoma cell lines SF295 and SF539 (Hama et al, 2004). Previously, we reported that brain is one tissue in which S1P is abundantly present .…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, LPA acts as an autocrine growth factor, and one or more LPA receptors are expressed in the prostate cancer cells (Xie et al, 2002). In astroglial cells as well, extracellularly added LPA induces the proliferation and migration of stimulated cells (Manning et al, 2000;Steiner et al, 2002;Malchinkhuu et al, 2003;Hama et al, 2004). Although there are enough studies related to LPAstimulated cell migration, the details of LPA signaling in migration have not been elucidated so far.…”
Section: Introductionmentioning
confidence: 99%
“…The cell motility-inducing activity of NPP2 depends on the production of bioactive lipids [384][385][386]. It is now thought that the major physiological functions of NPP2 result from its phospholipase activity [387].…”
Section: General Properties and Functional Rolementioning
confidence: 99%
“…Ki16425 blocks the LPA-induced motility of various LPA 1 -expressing carcinoma cell lines in vitro (18). Ki16425 also dosedependently inhibited LPA-induced proliferation of LPA 1 -expressing MDA-BO2͞GFP and CHO␤ 3 wt cell lines in vitro (Fig.…”
Section: Progression 3-(4-[4-([1-(2-chlorophenyl)ethoxy]carbonyl Amimentioning
confidence: 99%